KERAGAMAN AKTINOMISETES KEPULAUAN WAIGEO, KABUPATEN RAJA AMPAT, PAPUA DAN POTENSINYA SEBAGAI PENDEGRADASI SELULOSADAN PELARUT FOSFAT - Arif Nurkanto (Research Center for Biology-Indonesian Institute of Sciences, 2008)
Some Actinomycetes isolated from Waigeo Raja Ampat Regency Papua have been identified. Those isolates were also characterized for their cellulolitic and phosphate solubilizing ability. Microscopic identification was based on Miyadoh (1997) and Holt (1994) methods.Actinomycetes could be identified by microscopic observation on spores, chain spore, hypha, aerial hypha and its pigmentation.The cellulolitic ability was observed by clear zone ratio in CMC medium and phosphate solubilizing activity by the same approach in Vikoskaya medium.From 139 Waigeo's Actinomycetes isolates which had been deposited in LIPI Microbial Collection (LIPIMC) were identified as 10 genera (Actinomadura, Actinoplanes, Microbiospora, Micromonospora, Nocardia, Pseudonocardia, Saccharopolispora, Streptomices, Streptosporangium and Thermomonospora). As much as 57.5% phosphate solubilizing actinomycetes and 82.7 % cellulolitic actinomycetes were detected.